Environmental and social determinants of thyroid cancer: A spatial analysis based on the Geographical Detector - Huo, Shirui; Liu, Ying; Sun, Anyi; Zhang, Bo (Frontiers in Endocrinology, 2022)
Thyroid cancer has increased sharply in China in recent years. This change may be attributable to multiple factors. The current study aimed to explore the environmental and social determinants of thyroid cancer. Incidence data from 487 cancer registries in 2016 were collected. 8 factors were considered, air pollution, green space, ambient temperature, ultraviolet radiation, ambient humidity, elevation, economic status, health care and education level. Geographical detector (measured by q statistic) was used to evaluate the independent and interactive impact of 8 factors on thyroid cancer. Social factors especially economic status and health care level (q>0.2), were most influential on thyroid cancer. Ultraviolet radiation, air pollution and temperature had more impact on female while green space and elevation had more influences on male. Enhanced effects were observed when two factors interacted. Spatially, economic status, health care, air pollution and were positively associated with thyroid cancer while education level, green space, and elevation were negatively related to thyroid cancer. Socio-environmental determinants and spatial heterogeneity of thyroid cancer were observed in this study. These findings may improve our understanding of thyroid cancer epidemiology and help guide public health intervention.